Optimal kidney exchange with immunosuppressants - Haris Aziz; Ágnes Cseh (Hungarian Academy of Sciences, Institute of Economics, 2019)
Potent immunosuppressant drugs suppress the body's ability to reject a transplanted organ up to the point that a transplant across blood- or tissue-type incompatibility becomes possible. In contrast to the standard kidney exchange problem, our setting also involves the decision about which patients receive from the limited supply of immunosuppressants that make them compatible with originally incompatible kidneys. We firstly present a general computational framework to model this problem. Our main contribution is a range of efficient algorithms that provide flexibility in terms of meeting meaningful objectives. We also show that these algorithms satisfy desirable axiomatic and strategic properties.
Keywords: C63; C78; 330; kidney exchange; immunosuppressant drugs; matching; complexity